[Re]claim 2013 - reconciliation of urban place & indigenous meaningfulness reintegration with ecological systems reclaiming infrastructure for a new typology - Van Rensburg, Rudolf Johannes (University of Pretoria, 2013)
Dissertation MArch(Prof)--University of Pretoria, 2012.